Efficacy of Ronopterin (VAS203) in Patients with Moderate and Severe Traumatic Brain Injury (NOSTRA phase III trial): study protocol of a confirmatory, placebo-controlled, randomised, double blind, multi-centre study - Tegtmeier, Frank; Unterberg, Andreas (Trials, 2020)
Traumatic brain injury is a leading cause of death and disability worldwide. The nitric oxide synthase inhibitor Ronopterin was shown to improve clinical outcome by enhancing neuroprotection in a phase IIa trial.
Gesehen am 02.04.2020